2013
DOI: 10.1128/aem.01814-13
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and Chemical Diversity of a Hybrid-Isoprenoid-Producing Streptomycete Lineage

Abstract: Streptomyces species dedicate a large portion of their genomes to secondary metabolite biosynthesis. A diverse and largely marine-derived lineage within this genus has been designated MAR4 and identified as a prolific source of hybrid isoprenoid (HI) secondary metabolites. These terpenoid-containing compounds are common in nature but rarely observed as bacterial secondary metabolites. To assess the phylogenetic diversity of the MAR4 lineage, complementary culture-based and culture-independent techniques were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 42 publications
2
30
0
Order By: Relevance
“…4 These observations are supported at the genomic level, with MAR4 strains averaging five ABBA prenyl-transferases per strain relative to less than one for other streptomycetes. 5 MAR4 hybrid isoprenoids encompass a diversity of structures including prenylated polyketides, phenazines, and pyrroles, and are of considerable interest due to their potent biological activities. 35 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 These observations are supported at the genomic level, with MAR4 strains averaging five ABBA prenyl-transferases per strain relative to less than one for other streptomycetes. 5 MAR4 hybrid isoprenoids encompass a diversity of structures including prenylated polyketides, phenazines, and pyrroles, and are of considerable interest due to their potent biological activities. 35 …”
Section: Introductionmentioning
confidence: 99%
“…5 MAR4 hybrid isoprenoids encompass a diversity of structures including prenylated polyketides, phenazines, and pyrroles, and are of considerable interest due to their potent biological activities. 35 …”
Section: Introductionmentioning
confidence: 99%
“…Terpenoids are considered to be widespread in actinomycetes by genome mining analysis (Citron et al 2012); however, the hybrid isoprenoids are relatively uncommon in prokaryotes for reasons that are not understood (Kuzuyama & Seto 2003). Although less than 40 hybrid isoprenoids have been isolated from actinomycetes (Daum et al 2009;Heide 2009;Che et al 2012Che et al , 2013Kaysser et al 2012), the significant structural diversity and biological activity of these compounds render actinomycetes as important sources for hybrid isoprenoids-related drug discovery (Gallagher et al 2010(Gallagher et al , 2013. Furthermore, the isoprene moiety seems to be essential for the biological activities of the hybrid isoprenoids and may contribute to the diversity in the biological activities (Kumano et al 2008 Research, 2014Vol.…”
mentioning
confidence: 99%
“…) (Prieto‐Davó et al ., ), while it is chemically closer to S. synnematoformans . Thus, our results support that the production of hybrid isoprenoids is a phenotypic trait that differentiates the two MAR4 clades (Gallagher et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Previous studies have suggested a relationship between MAR4 phylogeny and hybrid isoprenoids production (Gallagher et al ., ) as well as to the number of gene clusters containing ABBA prenyltransferases (Gallagher and Jensen, ), which are the biosynthetic enzymes that have been reported to install isoprene units on target molecules and as such may regulate the bioactivity of molecules (Leipoldt et al ., ). Our results support the proposed relationships between evolutionary traits and secondary metabolite production which may be derived from homologous recombination of secondary metabolite genes resulting in highly specific metabolites for diverse niches (Jenke‐Kodama et al ., ), with the exception of strain PTM‐081, as stated above.…”
Section: Resultsmentioning
confidence: 99%